Clinical outcomes in patients with neurological disorders following periacetabular tumor removal and endoprosthetic reconstruction of the hemipelvis - Wang, Jichuan; Zhao, Zhiqing; Liang, Haijie; Niu, Jianfang; Liu, Xingyu; Wang, Han; Yang, Yi; Yan, Taiqiang; Guo, Wei; Tang, Xiaodong (Frontiers in Surgery, 2024)
Surgical treatment of musculoskeletal tumors in the periacetabular region present extremely difficult due to the complex anatomy and need for reconstruction. Orthopedic surgeons face more difficulties in patients with neurological conditions, which can cause increased muscle tone, an elevated risk of fractures, and compromised bone quality. There is limited evidence regarding endoprosthetic reconstruction for periacetabular tumors in individuals with neurological disorders.We conducted a single-center retrospective study to examine the outcomes of patients with preexisting neurological conditions who underwent surgery to remove periacetabular tumors and who underwent endoprosthesis reconstruction. Clinical presentation, detailed neurological conditions, complications, and functional outcomes were studied.Sixteen out of the 838 patients were identified (1.91%), with a mean follow-up time of 33 months. The primary neurological conditions encompassed Parkinson's disease, Alzheimer's disease, dementia, and cerebral ischemic stroke. Every patient was diagnosed with periacetabular lesions that were either primary or oligometastatic. They underwent tumor resection and subsequently received endoprosthetic reconstruction of the hemipelvis. Three patients developed metastasis lesions later, and two patients experienced tumor recurrence. Five cases experienced hip dislocation-one with periprosthetic fracture and one with surgical site infection. The position of the prosthetic rotating center was not correlated with dislocation. The reoperation rate was 31.25%. The cohort of patients all presented with more extended hospital stays and rehabilitation. In 3 patients, the general functional score was good, while in 6 patients, it was fair; in 7 patients, it was regarded as poor. The average MSTS93 score was 49.71%.Endoprosthetic reconstruction after periacetabular tumor resection is an effective way to eliminate tumors and salvage limbs. However, this group of patients has an increased likelihood of secondary surgery, complications, extended hospital stay, and no significant improvement in functional outcomes. Despite the diverse nature of the cohort, it is recommended to consider enhanced soft tissue reconstruction, supervised functional recovery and rehabilitation training.